DETAILED LAND REGISTRATION MECHANISM AND ITS LEGALITY IN MAKASSAR CITY FROM THE PERSPECTIVE OF THE HISTORICAL SCHOOL - Andi adinda Asty Maharaja; Lego Karjoko; Airlangga Surya Nagara (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the legal validity of landholding based on rincik within Indonesia’s land law architecture and the registration mechanism in Makassar from a historical school perspective. The objectives are to map the status of rincik as an old title record, to explain administrative conversion toward land certificates via sporadic registration and PTSL, and to test the evidentiary space of rincik in civil disputes. The method is normative legal research using statutory and historical approaches, reinforced by dogmatic interpretation, hermeneutic reading, and field inquiry with land officials. The legal frame covers UUPA Article 19 and Government Regulation 24 of 1997 Articles 23, 24 paragraph 2, 26, and 32 paragraph 1, as well as ATR BPN Regulation 6 of 2018 and Presidential Instruction 2 of 2018. Findings position rincik as preliminary juridical data with conditional probative value that may be recognized when authenticity is proven, long term possession exceeding twenty years is shown, credible witnesses are presented, fiscal duties are evidenced, and spatial consistency with surveys is demonstrated. The registration mechanism covers application submission, juridical verification, physical survey, thirty day public announcement, rights determination, and certificate issuance. Jurisprudence from Makassar in Andi Baso Matutu confirms a corridor for non certificate documents, where a verified rincik supported by possession, witnesses, and data integrity may culminate in a final and binding judgment and execution. The results affirm the certificate as the strongest title while recognizing rincik as an evidentiary gateway and a basis for conversion toward certification through PTSL.